The Application of Filter Cake Compost to Improve The Efficiency of Inorganic Fertilizer in Upland Sugarcane (Saccharum officinarum L.) Cultivation - Dharend Lingga Wibisana; Purwono Purwono; Sudirman Yahya (Universitas Muhammadiyah Yogyakarta, 2020)
The production of sugarcane in 2018 decreased due to the change in the cultivation method from lowland to upland. This research aimed to study the responses of growth and yield of two sugarcane varieties to the application of filter cake compost and inorganic fertilizer in upland sugarcane cultivation. This experiment was arranged in a split-split plot design consisting of three-factors, which were sugarcane varieties, the levels of filter cake compost, and the rates of inorganic fertilizer, assigned to the main plot, sub-plot, and sub-sub plots, respectively. The two sugarcane varieties were PS 881 and PS 862. The three levels of filter cake compost were 0, 5, 10 tons ha-1, and the four rates of inorganic fertilizers (percent of recommended dosage) were 25%, 50%, 75%, and 100%. The results showed that the growth and yield of PS 862 was better than that of PS 881, shown in the plant height, stem diameter, number of stems, and the length of internodes. The use of filter cake compost at a dose of 5 tons ha-1 was more efficient, and it could provide an efficiency of 0.097 tons per kg of cane at a dose of 76.76% inorganic fertilizer. Yet, it cannot reduce the use of inorganic fertilizer in producing sugarcane yield.